COOL potatoes? Poland plans to introduce mandatory country of origin labelling for fresh potatoes. (March 2019) - CARREÑO, Ignacio; MEDINA PÉREZ, Lourdes
Abstract : On 14 November 2018, Poland's Ministry for Agriculture and Rural Development notified the European Commission (hereinafter, Commission) of its intention to introduce mandatory country of origin labelling (hereinafter, COOL) for potatoes on the basis of a Draft Regulation of the Minister for Agriculture and Rural Development amending the Regulation on the labelling of certain foodstuffs (hereinafter, Draft Regulation). 1 Poland's notification is the most recent example of the continuously increasing number of EU Member States' measures on COOL for foodstuffs. While the EU already provides COOL requirements for fruits and vegetables in Regulation (EU) No 543/2011 of 7 June 2011 laying down detailed rules for the application of Council Regulation (EC) No 1234/2007 in respect of the fruit and vegetables and processed fruit and vegetables sectors 2 (hereinafter, Regulation (EU) No 543/2011), they do not apply to fresh potatoes.